Uteroplacental insufficiency programs regional vascular dysfunction and alters arterial stiffness in female offspring - Mazzuca, Marc Q (Blackwell Science Inc, 2010)
Intrauterine growth restriction caused by uteroplacental insufficiency increases the risk of cardiovascular disease in adulthood. Vascular mechanisms in female offspring are poorly understood. The aim of this study was to investigate the effects of uteroplacental insufficiency on blood pressure, vascular reactivity and arterial stiffness in four vascular beds in female offspring born growth restricted. Uteroplacental insufficiency was induced on day 18 of gestation in Wistar Kyoto rats by bilateral uterine vessel ligation (Restricted) or sham surgery (Controls). Wire and pressure myography were used to test endothelial and smooth muscle function, and passive mechanical wall properties, respectively, in uterine, mesenteric, renal and femoral arteries of 18-month-old female offspring. Collagen and elastin fibres were quantified using circular crossed-polarized light microscopy and quantitative real time polymerase chain reaction. Restricted female offspring were born 10–15% smaller. Restricted females were normotensive, had plasma triglycerides 2-fold elevated and had uterine endothelial dysfunction, attributed to a 23% reduction in the maximal relaxation produced by endothelium-derived hyperpolarizing factor. Uterine artery stiffness was increased, with an augmented proportion of thick and decreased proportion of thin collagen fibres. Vascular reactivity and mechanical wall properties were preserved in mesenteric, renal and femoral arteries in growth restricted females. Female offspring born growth restricted have selective uterine artery endothelial dysfunction and increased wall stiffness. The preserved vascular function in other arteries may explain the lack of hypertension in these females. The uterine artery specific dysfunction has potential implications for impaired pregnancy adaptations and a compromised intrauterine environment of the next generation.